Towards a network management solution for vehicular delay-tolerant networks - Ferreira, Bruno Filipe Aguiar Durães (2012)
Vehicular networks appeared as a new communication solution where vehicles act as a communication infrastructure, providing data communications through vehicle-to-vehicle (V2V) or vehicle-to-infrastructure (V2I) communications. Vehicular Delay-Tolerant Networks (VDTNs) are a new disruptive network architecture assuming delay tolerant networking paradigm where there are no end-to-end connectivity. In this case the incial node transmits the data to a closed node, the data will be carried by vehicles, hop to hop until the destination. This dissertation focuses on a proposal of a network management solution, based standard protocol Simple Network Management Protocol (SNMP) to VDTN networks. The developed solution allows control a VDTN netowork through a Network Management System (NMS) with the objective to detect and, if it’s possible, anticipate, possible errors on network. The research methodology used was the prototyping. So, it was built a network management module to the laboratorial prototype, called VDTN@Lab. The system built include a MIB (Management Information Base) placed in all vehicular network nodes. The solution was built, demonstrated, validated and evaluated their performance, being ready for use.